Natural enemies for the cabbage webworm, Hellula undalis (Fabr.)(Lepidoptera: Pyralidae) in Malaysia - A. Sivapragasam; Tock, Hing Chua (Springer-Verlag, 1997)
Four species of larval parasitoids were reared from larvae of the cabbage webworm (CWW), Hellula undalis (Fabr.) (Pyralidae: Glaphyriinae) collected from various cruciferous plants and a capparidaceous weed, Cleome rutidosperma (DC). On cabbage, only two species were record ed, viz, Bassus sp. (Braconidae) and Trathala flavoorbitalis (Cam.) (Ichneumonidae). The other parasitoids were braconids, Che/onus sp. and Phanerotoma sp. Egg or pupal parasitoids were not recorded. The parasitoids were not an important mortality factor of CWW on cabbage because they were usually present at the end of the crop season and their numbers were generally low. On the other hand, predator-exclusion experiments indicated that predators were important in determining the density of CWW on cabbage and the within-generation survival in the field. The major predator was the fire-ant, Solenopsis geminata (F.), which foraged on the prepupae and pupae.